The aging of the unions in West Germany, 1980 - 2006 - Claus Schnabel; Joachim Wagner (Institute for the Study of Labor (IZA), 2008)
Using data from the social survey ALLBUS for West Germany in the period 1980 to 2006, this paper demonstrates that union members are on average older than non-unionized employees. The probability of being unionized shows the inverted U-shaped pattern in age conjectured by Blanchflower (BJIR 2007) only in very few years. It is demonstrated that both intra-cohort change and cohort replacement effects have played a roughly equal role in the substantial fall in union density since 1980. If older cohorts with high densities continue to be replaced by young cohorts with low densities, average union density will fall further.
urn:nbn:de:101:1-20080828365
Keywords: J51; 330; Union membership; union density; cohort effects; West Germany; Gewerkschaft; Mitgliedschaft; Altersstruktur der Bevölkerung; Alte Bundesländer; Deutschland